2023
DOI: 10.2166/aqua.2023.211
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of acid and basic dye from the simulated wastewater using carbonized microplastic particles synthesized from recycled polyethylene terephthalate plastic waste bottles: an integrated approach for experimental and practical applications

Abstract: This study emphasizes the possible utilization of carbonized microplastic particles (CMPs) prepared from polyethylene terephthalate (PET) plastic bottle waste for dye adsorption. Methylene blue (MB) and methyl orange (MO) are adsorbed in a batch experiment to determine the effects of various experimental factors, including contact time (1–210 min), solution pH (3–11), adsorbent dosage (1–20 g/L), temperature (25–600 °C), and initial dye concentration (5–70 mg/L). The variance analysis (ANOVA) results of respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This displays the probable uses of both adsorbents for eliminating AR 27 from industrial wastewater. Chakraborty et al [ 58 ] found similar results for adsorption acid and basic dye using carbonized PET plastic microplastic particles.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…This displays the probable uses of both adsorbents for eliminating AR 27 from industrial wastewater. Chakraborty et al [ 58 ] found similar results for adsorption acid and basic dye using carbonized PET plastic microplastic particles.…”
Section: Resultsmentioning
confidence: 76%
“…The thermodynamic study represents the role of temperature for adsorption, the nature of the linkage between adsorbate and adsorbent, direction and mechanism of reaction with changing the experimental temperature [ 58 ]. These study results are presented in Table 5 , and Fig 3B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive ΔS 0 also suggest that lessening chance between the MOSWC and MO dye molecules interface, which mainly occurred through the chemical adsorption mechanism through the ion exchange process. Chakraborty et al [ 54 ] detect the exothermic reaction for dye adsorption using carbonizes adsorbent.…”
Section: Resultsmentioning
confidence: 99%